Antimicrobial and phytochemical screening of Hyptis suaveolens (L.Poit) Lamiaceae - Dharasurkar1, G.L. Pachkore1, *D.A. Dhale2, and A. N. (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present communication deals with the antimicrobial and preliminary phytochemical screening on the Hyptis suaveolens (L. Poit) Lamiaceae. The plant is stimulant, carminative, antispasmodic antirheumatic, antisuporitic bath. It is also used for parasitical cutaneous diseases, infection of uterus, and as sudorific in catarrhal condition, headache, stomach, snuff to stop bleeding of the nose. The antimicrobial effect of H. suaveolens leaves extract was evaluated aqueous and ethanol extracts was carried out by using fungus like, Canidida albicans, Collectrotrichum capsici, Fusarium oxysporum F. sp. Lycopersici, and four bacteria viz. Klebsiella pneumoneae, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. The aqueous extract of plant material can not show any inhibition zone microbes like C. albicanas, S. aureus and P. aeruginosa. All the seven microbes tested are susceptible to ethanol extract with the inhibition zone range of 12 – 29 mm. The in vitro antimicrobial evaluation was carried out by agar disc-diffusion method. Preliminary phytochemical screening shows the presence of volatile oil, starch, proteins, tannins, saponins, fats, alkaloids and glycosides etc.